Development of a Cooking Class Learning Model to Stimulate Fine Motor Skills in Early Childhood Education - Nur Indah Sari (Marasofi International Media and Publishing (MIMP), 2026)
Fine motor skill development is an important aspect of early childhood education because it supports children’s readiness for learning and daily independence. However, many early childhood learning activities are still dominated by conventional approaches that provide limited opportunities for hands-on experiences. This study aimed to develop and implement a Cooking Class Learning Model to stimulate fine motor skills among children aged 5–6 years. The study employed a quantitative approach using a pre-experimental design conducted at RA Baitul Ibadah, Binjai Barat District, involving 40 children divided into experimental and control classes. Data were collected through observation sheets, pretest-posttest assessments, documentation, and analyzed using descriptive statistics, N-Gain analysis, normality tests, homogeneity tests, and independent sample t-tests. The results showed that the experimental class achieved a higher posttest mean score (37.55) compared to the control class (26.75). The average N-Gain score of the experimental class reached 66.35%, while the control class obtained 29.16%. Hypothesis testing also indicated a significant difference between both groups with a significance value of 0.000 < 0.05. These findings indicate that the Cooking Class Learning Model effectively improves children’s fine motor skills through practical and child-centered learning experiences. Therefore, this model is recommended as an innovative learning approach for early childhood education institutions to support active and experiential learning environments.